The Influence of Problem-Based Learning Models and Critical Thinking Ability on Learning Outcomes - Nia Fatmasari; Darmansyah Darmansyah; Indrati Kusumaningrum; Abna Hidayati (Postgraduate School, Universitas Negeri Padang, 2021)
This research started from the low student learning outcomes of PAI, this can be seen in the learning outcomes obtained by students, observations, interviews with teachers. This study aims to determine the effect of applying a problem-based learning model on the learning outcomes of class X PAI students of SMAN 1 V Koto Kampung Dalam Padang Pariaman. This type of research is a quasi-experimental research. The population in this study were all students of class X, totaling 248 and consisting of 9 classes. The sample used is selected based on values that have almost the same average. The sample in this study were students of class X IPS 3 as the experimental class and class X IPS 4 as the control class.